La Signora dei sogni origini e visioni dell’alchimia ellenistica - Albrile, Ezio (Archaeus, 2005)
Central and Eastern European Online Library - CEE journals, documents, articles, periodicals, books available online for download, Zeitschrfitendatenbank, Online Zeitschriften, Online Zeitschriftendatenbank